Ratios of Free to Total Prostate-Specific Antigen and Total Prostate Specific Antigen to Protein Concentrations in Saliva and Serum of Healthy Men - Ayatollahi, Hossein; Darabi Mahboub, Mohammad Reza; Mohammadian, Nema; Parizadeh, Mohammad Reza; Kianoosh, Tayyebeh; Khabbaz Khoob, Mahdi; Kamalian, Fahimeh (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0; @font-face font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: We evaluated the ratio of free to total prostate-specific antigen (PSA) and PSA to protein concentrations in saliva and serum of healthy men. Materials and Methods: Concentrations of protein, free PSA, and total PSA in serum and saliva were measured in 30 healthy men aged 42 to 73 years, and their ratios were compared between the two fluids. Results: There was a significant direct correlation between serum free-total PSA ratios of serum and saliva (P = .04) and between total PSA-protein ratios of serum and saliva (P = .02). Also, there were significant correlations between total and free PSA levels in saliva (P = .05) and between those in serum (P < .001). Significant inverse and direct correlations were detected between the body mass index and serum values of total PSA-protein (P = .04) and free-total PSA (P = .01), respectively. Conclusion: We can use saliva sample instead of serum sample for estimation of free-total PSA and total PSA-protein levels in men without prostate diseases. There is, however, a pressing need for much additional research in this area before the true clinical value of saliva as a diagnostic fluid can be determined.